SOLUSI PERSAMAAN DIFERENSIAL PADA SISTEM BEJANA DENGAN MENGGUNAKAN METODE TRANSFORMASI LAPLACE - Risnawati Ibnas; Putri Resky Hasyim; Muhammad Ridwan (Teknosains, 2020)
The purpose of this study is to obtain the results of the completionof the Differential Equations in the Vessel System using the LaplaceTransform Method. advantage of the Laplace transform is that the initialvalue problem of a linear differential equation can be solved directly withoutfirst determining the general solution and also to obtain the maximum benefit.The model that has been obtained in-vessel systems is homogeneous nonlineardifferential equation: if we want to obtain total we must be taken aggregate from a general solution and special solution, the result is